Direct evidence and quantification of homologous recognition between DNA duplexes - Andrew Stannard; Ehud Haimov; Jonathan G. Hedley; Yaxuan Xiao; Marco Di Antonio; Gleb Oshanin; Claudia Danilowicz; Mara Prentiss; Lorenzo Di Michele; Alexei A. Kornyshev (Proceedings of the National Academy of Sciences, 2026)
Stretches of double-stranded DNA sharing the same sequence can recognize each other in cells. This phenomenon, known as homologous recognition, is essential for DNA recombination and repair. Yet, its mechanism remains debated, with purely physical interactions proposed as a contributing factor. Here, we use a minimal DNA nanosensor to quantify homologous pairwise interactions with exquisite precision. We find that homology enhances the duplex–duplex affinity induced by physiological divalent cations and measure the homology-driven recognition free energy as ∼ − 0.01 kcal / mol per base pair. This affinity substantially enhances coalignment of homologous DNA in the confined geometry of the nanosensor, which mimics physical effects of concentrated biological environments. We introduce a quantitative electrostatic framework that attributes this emergent behavior to coherent charge distributions unique to homologous DNA. Our findings provide compelling evidence in support of purely physical sequence-specific interactions between intact double-stranded DNA, which may bear biological relevance for homologous recombination.